Literacy and Reading Interest Improvement Movement at the Medan Orphanage - Zalukhu, Febius; Manullang, Randeska; Meutia, Zahara; Saragih, Lenti Susanna; Andi; Irma Herliza Rizki (Outline Publisher, 2025)
Children's reading and literacy interests are important foundations for developing knowledge, skills, and character. Orphans, as a vulnerable group, often face limited access to reading materials and literacy facilities, thus requiring special attention to improve their reading skills and learning interests. This research and community service activity aims to develop an effective literacy movement in orphanages in Medan through book lending programs, interactive reading lessons, group discussions, and literacy-based creative activities. The method used is a participatory action approach, including identifying needs, developing literacy modules, implementing shared reading activities, mentoring, and evaluating reading interests. The implementation results show a significant increase in children's reading frequency, reading comprehension, discussion skills, and learning motivation. This program has a positive impact on learning independence, character development, and awareness of the importance of literacy for orphans. These findings confirm that a literacy movement based on active participation can be a model for sustainable non-formal education empowerment for vulnerable groups.